Closing the gap: improving the percentage of Annual Wellness Visits among Medicare patients - Andrew Martin; Brittany Strelow; Rachel Olson; Danielle O'Laughlin; Sean Curran; Joshua Perry; Vincent Hurley; Colleen Costello; Majken Wingo (BMJ Open Quality, 2024)
Background The Medicare Annual Wellness Visit (AWV) allows providers to acquire critical information about patients’ health through a review of vitals, environmental risks, and medical and family history. These visits are free to those enrolled in Medicare and prioritize patient–provider relationship building and preventative care. Despite this, AWV completion rates are suboptimal.Methods A quality improvement project was aimed to increase the percentage of AWVs among Medicare patients in a primary care internal medicine practice from a baseline of 1.7% completion to 2.7% in 3 months from January to April 2023.Intervention With eligible patients identified, a standardized approach was created where an AWV appointment was ordered, and a patient message explaining the benefit of the appointment was sent by the patient portal.Results Our AWV intervention resulted in 72 patients being seen for an AWV, which increased the percentage of completed AWVs in the division by 2.1% from 1.7% to 3.8% in 3 months.Conclusion This intervention will continue to improve AWV rates and improve patient care for Medicare patients in internal medicine. It could be applied to other areas of primary care and within other health systems.